Primary Care, Health-Behavior Groups. (27th January 2017) - Ellis, Carilyn
ABSTRACT: Due to the increased physical, emotional, and financial burden of chronic health conditions on patients and the larger medical community, efforts have intensified to provide health-behavior focused group therapy in primary care settings. The goal of these groups is to increase access for patients who may be hesitant to engage in more traditional mental health services due to stigma, and to reduce medical costs and improve overall emotional and physical health of patients with chronic conditions. Groups are focused on providing patients with the information and tools they need to understand and improve their conditions. Success is measured by increase in knowledge and behavioral action in group members. Interventions provided in primary care are brief, solution-focused, and contextually relevant. A skilled primary care clinician leading a health-behavior group will unify participants around common themes and foster focus on the health-related topic while adjusting to the their contextual needs.